Identification of Mangrove using DNA Barcoding and Vegetation Analysis at the Sarawet Mangrove Ecotourism Site, North Minahasa Regency - Rondonuwu, Sendy B; Maabuat, Pience; Kamu, Vany; Pujiastuti, Dwi Rahayu (Universitas Sam Ratulangi, 2026)
This study aims to identify the diversity of mangrove species in the Mangrove Ecotourism area of Sarawet Village, Likupang, North Minahasa Regency, using a molecular taxonomy approach based on DNA barcoding and an ecological approach through vegetation analysis. Vegetation data collection was conducted descriptively and qualitatively using transect and plot methods. Molecular analysis included DNA extraction from mangrove leaf samples, amplification of the matK and rbcL genes using Polymerase Chain Reaction (PCR), followed by sequencing and nucleotide base comparison using the Basic Local Alignment Search Tool (BLAST). The morphological vegetation analysis found six mangrove species at the research site, namely Rhizophora mucronata, Rhizophora apiculata, Bruguiera sp., Sonneratia alba, Aegiceras corniculatum, and Ceriops tagal. Meanwhile, the molecular identification results of DNA barcoding showed that the matK gene sequence in the SRA sample had a 99.98% similarity with Sonneratia alba, and the rbcL gene sequence in the SRC sample had a 100% similarity with Aegiceras corniculatum. The combination of molecular identification and vegetation analysis provides accurate data on mangrove species composition, which is highly essential as a foundation for monitoring, sustainable management, and conservation of the mangrove ecotourism area as a buffer zone.